Optical and photoconductive properties of indium sulfide fluoride thin films - Vygranenko, Yuri (2019)
This work reports on transparent semiconducting indium sulfide fluoride (ISF) thin-films exhibiting high sensitivity to ultraviolet radiation. The films were deposited on fused silica and silicon substrates using a radiofrequency plasma-enhanced reactive thermal evaporation system. The deposition was performed evaporating pure indium in SF6 plasma at a substrate temperature of 423 K. Rutherford backscattering measurements were used to determine the chemical composition of the films deposited on silicon substrates. The surface morphology was studied using scanning electron microscopy technique. The film characterization includes electrical, optical, and photoconductivity measurements. The synthesized compound is highly-resistive (similar to 700 M Omega-cm at 300 K) and exhibits an evident semiconducting behavior. The activation energy of 0.88 eV is deduced from the temperature dependence of electrical resistivity. The indirect band energy gap of 2.8 eV is determined from transmittance spectra of the ISF films. The photoconductivity band is centered at 345 nm wavelength. The photoconductivity spectrum also shows the Urbach tail with a characteristic energy of 166 meV. ISF is a promising candidate for a buffer layer in chalcogenide-based solar cells.